Ministry of International Trade and Industry Wilayah Persekutuan , Kuala Lumpur / Muhammad Daniel Abd Manap ... [et al.] - Abd Manap, Muhammad Daniel; Ismail, Mohammad Izz Hirzi; Bokhari, Muhammad Amzar Aiman; Ahmad, Aisyah Maheerah; Tengku Zainuddin, Tengku Noor Fatin (Universiti Teknologi Mara, Perak, 2016)
Integrated Final Project is a subject comprising of various aspects of the building industry. Emphasis will be given to the aspects of organizational management , technology , design , property , building economic , financing , law , communications , project planning and management. The subject encompasses and integrates all courses studied in the Diploma program. The main objectives of this subject is to teach student on how to produce a report and an effective presentation of the case study. Then , to justify the relationship of various professionals and their practices in the building industry as well as the integration and cross subject analysis and synergy. Besides , to describe a multi-disciplinary approach to problem solving encountered in a the final project and to reinforce the wide array of skills , knowledge and applications necessary for the successful completion of project and teamwork. The research will be focusing on the details of the property , organizational maintenance management , maintenance policy , planning , programme , building design & technology , building condition assessment , maintenance strategy , legal aspect , financial budget and the recommendation to the problems statement. There are different method of research being used in this report which are throughout the site visit at the case study and observation on the site. Besides , there is a interview with the representative person from the related department to gained information to fulfill the task requirement. Then , the data collection from the monthly report and building plan that will be gathered in the final report. The last method of research is through the journal , books and internet sources as references. The photograph in the report as evidence of the research on site and one the research method.